2022
DOI: 10.3390/ijms23158800
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Peptides Human β-Defensins Induce the Secretion of Angiogenin in Human Dermal Fibroblasts

Abstract: The skin produces a plethora of antimicrobial peptides that not only show antimicrobial activities against pathogens but also exhibit various immunomodulatory functions. Human β-defensins (hBDs) are the most well-characterized skin-derived antimicrobial peptides and contribute to diverse biological processes, including cytokine production and the migration, proliferation, and differentiation of host cells. Additionally, hBD-3 was recently reported to promote wound healing and angiogenesis, by inducing the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Furthermore, HBD-2 has different effects on fibroblast activity in connective tissue. A study conducted in 2022 by Umehara et al showed that HBD-2 induces angiogenin secretion via dermal fibroblasts, supporting angiogenesis, which is particularly beneficial in chronic wounds [71]. HBD-2 also induces human conjunctival fibroblast proliferation, gene expression, and the synthesis of fibroblast collagenase (MMP1), which is required for extracellular matrix remodulation and supporting cell migration during wound healing [72].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HBD-2 has different effects on fibroblast activity in connective tissue. A study conducted in 2022 by Umehara et al showed that HBD-2 induces angiogenin secretion via dermal fibroblasts, supporting angiogenesis, which is particularly beneficial in chronic wounds [71]. HBD-2 also induces human conjunctival fibroblast proliferation, gene expression, and the synthesis of fibroblast collagenase (MMP1), which is required for extracellular matrix remodulation and supporting cell migration during wound healing [72].…”
Section: Discussionmentioning
confidence: 99%
“…19 HBDs also function in angiogenesis by promoting angiogenin production in dermal fibroblasts. 45 Whether dermal fibroblasts express other antimicrobial peptides upon microbial challenge is less well understood. However, recent work has observed that a subcluster of dermal fibroblasts can proliferate and differentiate into adipocytes, releasing plenty of antimicrobial peptide cathelicidin in response to S. aureus dermal infection.…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…An in vitro study has shown that human α‐defensin 5 (HD5) and HBD2 are released by cultured primary dermal fibroblasts after stimulation of DENV 19 . HBDs also function in angiogenesis by promoting angiogenin production in dermal fibroblasts 45 . Whether dermal fibroblasts express other antimicrobial peptides upon microbial challenge is less well understood.…”
Section: Effector Molecules Produced By Dermal Fibroblastsmentioning
confidence: 99%
“…Umehara et al studied the well-characterized skin-derived human β-defensins antimicrobial peptides and demonstrated their influence on the secretion of angiogenin, a potent angiogenic factor. They revealed that various human β-defensins can stimulate the production of angiogenin while maintaining their antimicrobial activities and other immunomodulatory properties [ 13 ]. Zhu et al identified a new antimicrobial peptide gene, the Sparanegtin gene from the mud crab Scylla paramamosain , whose transcripts were particularly abundant in the testis of that species.…”
mentioning
confidence: 99%